2002
DOI: 10.1007/s00464-001-8313-5
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic improvement in gastroesophageal reflux disease (GERD) following laparoscopic Roux-en-Y gastric bypass

Abstract: LRYGBP results in very good control of GERD in morbidly obese patients with follow-up as late as 3 years. Morbidly obese patients who require surgery for GERD may be better served by LRYGBP than fundoplication because of the additional benefit of significant weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
147
0
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(154 citation statements)
references
References 29 publications
3
147
0
4
Order By: Relevance
“…For the morbidly obese patient who wants to lose weight and who has significant reflux symptoms but has failed weight loss programs, a Roux-en-Y gastric bypass may be the procedure of choice, as laparoscopic fundoplication will not address the issue of weight reduction. This operation provides excellent long-term relief of GORD 3,[16][17][18] and has the added benefit of long-term weight loss and the associated health benefits. LARS has been found to be as equally effective as a gastric bypass in the morbidly obese in relieving reflux symptoms, 20 and should still be offered to patients who do not desire bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%
“…For the morbidly obese patient who wants to lose weight and who has significant reflux symptoms but has failed weight loss programs, a Roux-en-Y gastric bypass may be the procedure of choice, as laparoscopic fundoplication will not address the issue of weight reduction. This operation provides excellent long-term relief of GORD 3,[16][17][18] and has the added benefit of long-term weight loss and the associated health benefits. LARS has been found to be as equally effective as a gastric bypass in the morbidly obese in relieving reflux symptoms, 20 and should still be offered to patients who do not desire bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%
“…These varied results of weight loss on GERD symptoms could be because of small sample size, gender differences, wide variation in BMI of subjects (23 vs. 43), and use of different weight loss methods (various lifestyle changes vs. surgical approaches) (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Furthermore, a number of lifestyle intervention treatments have been attempted for GERD-low calorie diet, use of fruits/ vegetables, and physical activity; individually each intervention has no direct correlation with GERD improvement as shown in previous population-based studies (13,22,23) and a recent meta-analysis (32).…”
Section: Discussionmentioning
confidence: 99%
“…Previous data on the impact of weight loss achieved through various lifestyle (dietary changes and physical activity) (21)(22)(23)(24)(25) or surgical methods (Roux-en-Y gastric bypass or vertical band gastroplasty) (26)(27)(28)(29)(30) on GERD symptoms are scarce and with conflicting results (31). A systematic review evaluating the effects of various life style changes on GERD symptoms suggested that weight loss and head of bed elevation could improve symptoms of GERD (32).…”
Section: Introductionmentioning
confidence: 99%
“…In 2002, Frezza and colleagues 23 assessed changes in GERD symptoms following LRYGB. 23 Of 152 patients who participated in the study, follow-up revealed an EWL of 64% and a significant reduction in GERD symptoms at 12-month follow-up (heartburn: 87%-22%, p < 0.001; water brash: 18%-7%, p < 0.05; wheezing: 40%-5%, p < 0.001; laryngitis: 17%-7%, p < 0.05; aspiration: 14%-2%; use of proton pump inhibitors: 44%-9%, p < 0.001; and use of H2 blockers: 60%-10%, p < 0.01).…”
Section: Roux-en-y Gastric Bypassmentioning
confidence: 99%